Dynamic Correlation Technique and Model Updating on Go Kart Chassis Structure - M. S. M., Sani; M. M., Rahman; M. M., Noor; K., Kadirgama; G. L., Ming (2008)
Chassis is a major component in a vehicle system. When the structure like chassis is excited at same value of natural frequency, resonance would occurred and damage the structure. The dynamic characteristic of go kart chassis such as the natural frequency and mode shape were presented using finite element analysis (FEA). The process of chassis design in the automotive was developed utilizing the advanced computer aided design. Structural modification and optimization are used to reduce component complexity, weight and subsequently the cost. Therefore, the model verification is needed before design decisions made in the FEA environment and it can be implemented in production with high confidence. Impact hammer test was carried out to validate the finite element (FE) model. Data analyzer was used to convert the response signal from the sensor which was in the time domain to frequency domain. The acquired result shows that the percentage of error for model updating is lower than initial FEA results. It indicates that the structural model updating technique is one of the method to give the better agreement between the experimental and computational results. Percentage of error reduced from 30% to below 11% for model updating of go kart structure. The purpose is to reduce the vibration as well as to improve the strength of the chassis.